2000
DOI: 10.3109/10253890009001122
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Are Neuroprotective in the Dentate Gyrus of Adrenalectomized Female Rats

Abstract: Neuroprotective effects of androgens have not been well-characterized, but there is evidence that 5 alpha-androstane-3 alpha, 17 beta-diol (3 alpha-diol) has anti-seizure effects. To further examine androgens' neuroprotective effects, testosterone (T), dihydrotestosterone (DHT), 3 alpha-diol (1.0 mg/kg SC daily), or sesame oil vehicle was administered to adrenalectomized or sham-operated, young, female Long Evans rats (N = 52). After seven days, animals were perfused and trunk blood was collected for radioimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 50 publications
1
20
1
Order By: Relevance
“…In adults, both androgens and estrogens have been shown to be neuroprotective in the hippocampus following adrenalectomy or kainic acid administration (Frye 2001; Frye and McCormick, 2000a,b; Veiga et al, 2003). Testicular surges of testosterone occur during the prenatal and early neonatal periods and these may inhibit the effects of DEX on apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, both androgens and estrogens have been shown to be neuroprotective in the hippocampus following adrenalectomy or kainic acid administration (Frye 2001; Frye and McCormick, 2000a,b; Veiga et al, 2003). Testicular surges of testosterone occur during the prenatal and early neonatal periods and these may inhibit the effects of DEX on apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In seizure-related lesion paradigms similar to our kainate model, Frye and colleagues found that acute androgen treatment reduced hippocampal damage (Frye and McCormick, 2000;Frye and Reed, 1998). Their data suggests a protective mechanism that involves inhibition of seizure activity by the DHT metabolite 5α-androstane-3α, 17β-diol (3α-diol) (Rhodes and Frye, 2004;.…”
Section: Androgens Regulate Neuron Viabilitymentioning
confidence: 96%
“…Early corticosterone exposure is necessary for dentate gyrus development of rodents and species-typical cognitive function (He et al, 2009) and glucocorticoid production from the adrenals promotes cell survival in the brain. Indeed, removal of the adrenals in rats increases cell death in the granule layer and dentate gyrus of the hippocampus (Frye and McCormick, 2000a,b; Rhodes et al, 2004). Moreover, co-administration of the 5α-reductase inhibitor, finasteride, with P 4 reinstatement attenuates these effects in ovariectomized females (Rhodes et al, 2004), suggesting that adrenally derived, 5α-reduced progestogens have important trophic effects to maintain limbic integrity.…”
Section: Neurodevelopmental Neuropsychiatric and Neurodegenerative mentioning
confidence: 99%